1990
DOI: 10.1093/rheumatology/29.1.10
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Congenital Heart Block: Association With Maternal Antibodies to Ro(ss-A) and La(ss-B)

Abstract: A case control study of congenital complete heart block (CHB) was undertaken to determine the degree of association of this condition with maternal connective tissue disease and with maternal autoantibodies, in particular those to Ro(SS-A). Mothers of cases (n = 18) and controls (n = 72) completed a self-administered questionnaire and donated 10 ml of blood. The odds of giving birth to a child with CHB were increased by a factor of 22 for women with antibodies to Ro(SS-A) and/or La(SS-B) compared with women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The relationship between CCHB in the developing fetus and maternal anti-Ro and anti-La antibodies is well established. [1][2][3][4][5][6][7]9 However, to date there have not been any large, prospective studies of serial fetal echocardiograms of pregnant women with anti-Ro and anti-La antibodies. We therefore undertook this study to determine the risk of development of CCHB in fetuses of all mothers with anti-Ro and anti-La antibodies regardless of maternal health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between CCHB in the developing fetus and maternal anti-Ro and anti-La antibodies is well established. [1][2][3][4][5][6][7]9 However, to date there have not been any large, prospective studies of serial fetal echocardiograms of pregnant women with anti-Ro and anti-La antibodies. We therefore undertook this study to determine the risk of development of CCHB in fetuses of all mothers with anti-Ro and anti-La antibodies regardless of maternal health.…”
Section: Discussionmentioning
confidence: 99%
“…The development of NLE and CCHB in the developing fetus is a recognized complication of pregnancy for women known to have anti-Ro and anti-La antibodies. [1][2][3][4][5][6][7][8][9] However, despite the presence of anti-Ro and anti-La antibodies in their sera, most mothers of children CCHB are asymptomatic at the time of delivery of the child with CCHB and at long-term followup. 3,4,7,10,11 Conversely, most women with a diagnosed autoimmune disease do not deliver children with CCHB.…”
mentioning
confidence: 99%
“…The relation between maternal connective tissue disease and complete congenital heart block (CCHB) in the fetus has been known for some time (Hogg 1957). Several groups have described serum antibodies to soluble ribonucleoproteins, anti‐Ro (SS‐A) and anti‐La (SS‐B), in the affected infants and their mothers (Kephart et al 1981; Franco et al 1981; Miyagawa et al 1981), and subsequent studies have demonstrated the almost universal association of CCHB with either or both of these autoantibodies (Scott et al 1983; Watson et al 1984; Weston et al 1982; Taylor et al 1988; Gross et al 1989; McCredie et al 1990). The heart contains onc of the body's highest concentrations of Ro (SS‐A) antigen (Wolin & Steitz 1984; Harley et al 1985; Deng et al 1987).…”
mentioning
confidence: 99%
“…One study has suggested a titre of > 1:16 to be of significance (Ramsey‐Goldman et al 1986). The presence of anti‐La (SS‐B) antibody in addition to the anti‐Ro (SS‐A) antibody (Provost et al 1987; McCredie et al (1990). Presence of HLA DR3 in the mother (Watson et al 1984; Lee et al 1983; Buyon et al 1987; Buyon et al 1988; Lockshin et al 1983). Ro (SS‐A) positive women giving birth to normal infants (i.e., absence of CCHB or neo‐natal lupus) are generally HLA‐DR2 (Watson et al 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation